'It's like sailing' – Experiences of the role as facilitator during moral case deliberation. (September 2017) - Rasoal, Dara; Kihlgren, Annica; Svantesson, Mia
Background: Moral case deliberation is one form of clinical ethics support, and there seems to be different ways of facilitating the dialogue. Purpose: This paper aimed to explore Swedish facilitators' experiences of their role in moral case deliberations. Method: This study had a qualitative approach with explorative design. Semi-structured interviews with eleven MCD facilitators were conducted. Their experiences were analyzed using thematic analysis. Result: Being a facilitator was understood through the metaphor of sailing: against the wind or with it. The role was likened to a sailor's set of skills: to promote security and well-being of the crew, to help crew navigate their moral reflections, to sail a course into the wind against homogeneity, to accommodate the crew's needs and just sail with the wind, and to steer towards a harbour with authority and expertise. Balancing the disparate roles of being accommodative and challenging may create a free space for emotions and ideas, including self-reflection and consideration of moral demands. Conclusion: This research opens the question of whether all these skills can be taught through systematic training or whether facilitators need to possess the characteristics of being therapeutic, pedagogical, provocative, sensitive and authoritarian.